Medical Deportations and Racial Narratives of the Burdensome Migrant. (November 2022) - Park, Lisa Sun-Hee
Hospitals across the U.S. are quietly removing severely injured and chronically ill migrants to other nations. It is a reality that exists in practice but not in policy and is experienced by hundreds, potentially thousands, of low-income uninsured migrants. There is no formal accounting or regulation of this practice and federal immigration authorities remain silent regarding this practice despite the fact that alien removals, or deportations, are solely within their jurisdiction. Focusing on a case study, this paper analyzes migrant narratives embedded within news media accounts and legal analyses of medical deportations to address how this controversial practice is rationalized by health care providers. In these accounts, a racialized narrative of migrants as public burdens was clearly evident. This paper argues that such narratives have the power to transform actions legally defined as illegal—such as medical deportations—into a reasonable practice. In this way, social "cost" is racialized into individual debt, allowing for seemingly extraordinary disciplinary actions that are contrary to normative policy and ethics.